Analysis of Risk Factors for Psychological Stress in Breast Cancer Patients: Observational Study in West Java, Indonesia - Pancakarsa, Eka Prasetya; Monty P. Soemitro; Arief Budianto; Maman Abdurahman; Kiki Ahmad Rizki; Yohana Azhar; Dodi L. H. L. Gaol (HM Publisher, 2024)
Background: Breast cancer is one of the most common types of cancer in women in Indonesia. Diagnosis and treatment of breast cancer can cause significant psychological stress in the sufferer. This study aims to analyze the risk factors for psychological stress in breast cancer sufferers in West Java, Indonesia using an observational study with multivariate analysis. Methods: This research involved 200 breast cancer sufferers recruited from hospitals in West Java. Data was collected using a questionnaire that measured psychological stress, demographic factors, social factors, and medical factors. Data analysis was carried out using multinomial logistic regression to identify risk factors associated with the occurrence of psychological stress. Results: The research results show that the incidence of psychological stress in breast cancer sufferers in West Java is 42%. Risk factors that are significantly associated with the occurrence of psychological stress are young age, unmarried marital status, low social support, high levels of anxiety, and advanced cancer stage. Conclusion: This research shows that several risk factors can increase the incidence of psychological stress in breast cancer sufferers in West Java. These findings can be used to develop more effective interventions to help breast cancer survivors cope with psychological stress.